The Impact of Load Traffic of Road Deterioration in Urban Areas: Case Study Jalan KH Abdul Halim Majalengka - Yusan Nurul Septiyani; Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2024)
Pavement road kingdom damage frequently becomes into a serious issue. Due to the possibility that it will increase maintenance costs, lower the quality of transportation, and increase the danger of accidents. Next, cross. Findings from research This anticipation may provide additional light on the mechanisms underlying the repercussions and cross-road load of damaged pavement. It may serve as a foundation for the creation of maintenance plans that are more successful. The primary thoroughfare with heavy traffic in Majalengka, Jalan KH Abdul Halim, served as the research location. The Importance Performance Analysis (IPA) approach, which is employed in Cartesian with four quadrants, is employed in this study. Data from the results questionnaire were used to determine the significance of road pavement degradation. Driving safety was the greatest indicator, scoring 4.81, while the frequency of maintenance and repairs received the lowest score of 4.57. Temporary satisfaction with road pavement damage, with a score of 2.43 for value data from the greatest indicator impacts on vehicles, and a score of 2.11 for value data lowest, which relates to the frequency of maintenance and repairs. Based on the aforementioned statistics, the average interest value is 4.71, the average satisfaction value is 2.26, and the average gap value is -2.45. According to the data research findings, road and pavement damage received an average relevance score of 4.71. Temporary, that is, the average satisfaction score of 2.26 indicates that the interest mark is taller than the satisfaction mark, resulting in an average gap value of -2.45; the negative sign indicates that the user's road to lighting satisfaction Not just yet can be satisfied, given that the respondents anticipate that the KH Abdul Halim Street road's damaged pavement will be repaired.